Perceived Effectiveness and Motivations for the Use of Web-Based Mental Health Programs: Qualitative Study - Eccles, Heidi; Nannarone, Molly; Lashewicz, Bonnie; Attridge, Mark; Marchand, Alain; Aiken, Alice; Ho, Kendall; Wang, Jianli (JMIR Publications, 2020)
BackgroundThe prevalence of depression is high and has been stable despite increased treatment, research, and dissemination. People encounter barriers to seeking traditional mental health services, which could be mitigated by using web-based prevention methods. ObjectiveThis study aims to understand what people at high risk for depression perceive as effective aspects of web-based mental health programs and what motivates people at high risk for depression to use web-based mental health programs. MethodsWe conducted an inductive content analysis using telephone interview data from 77 participants at high risk for depression who were recruited from 2 randomized controlled trials (RCTs). Participants from the first RCT were working men who had been randomly assigned to 1 of the following 3 groups: control group, who had access to general depression information from a website called BroMatters; intervention group 1, who had access to the BroMatters website along with the associated BroHealth web-based mental health program; and intervention group 2, who had access to the BroMatters website, the BroHealth web-based mental health program, and telephone sessions with a life coach. Participants from the second RCT were men and women who had been assigned to the intervention group, who received access to the HardHat web-based mental health program, or the control group, who only received access to the HardHat web-based mental health program following completion of the RCT. Participants for this inductive content analysis study were recruited from the intervention groups in both RCTs. Two groups of participants (n=41 and n=20) were recruited from the BroHealth RCT, and a third group comprised 16 participants that were recruited from the HardHat RCT. ResultsWe generated four categories regarding the perceived effectiveness of web-based programs and five categories related to what motivates the use of web-based programs. Participants identified awareness, program medium and functionality, program content, and coaches as categories related to the effectiveness of the programs. Categories of motivators to use web-based programs included providing reminders or incentives, promotion of the programs, providing appropriate medium and functionality, appropriate content, and perceived need. The final category related to motivators reflects perceptions of participants who were either unsure about what motivates them or believed that there is no way to motivate use. ConclusionsConflicting evidence was obtained regarding the perceived effectiveness of aspects of the content and functionality of web-based programs. In general, web-based mental health programs were perceived to help increase mental health awareness, especially when it includes live access to a coach. However, the results also revealed that it is difficult to motivate people to begin using web-based mental health programs. Strategies that may motivate the use of such programs include perceived personal need, effective promotion, providing incentives and reminders, and improving functionality.